If the magic fits - Schmid, Susan Maupin (Schmid, Susan Maupin. 100 dresses, 2016)
Darling Dimple, a young orphan, discovers a closet full of magical dresses, each of which gives her the appearance of another person in the castle and that, along with her own magical abilities, helps her protect Princess Mariposa from betrayal as the castle swarms with suitors.